Combined organic–inorganic fouling of forward osmosis hollow fiber membranes - Arkhangelsky, Elizabeth (2013)
This research focused on combined organic–inorganic fouling and cleaning studies of forward osmosis (FO) membranes. Various organic/inorganic model foulants such as sodium alginate, bovine serum albumin (BSA) and silica nanoparticles were applied to polyamide-polyethersulfone FO hollow fiber membranes fabricated in our laboratory. In order to understand all possible interactions, experiments were performed with a single foulant as well as combinations of foulants. Experimental results suggested that the degree of FO membrane fouling could be promoted by synergistic effect of organic foulants, the presence of divalent cations, low cross-flow velocity and high permeation drag force. The water flux of fouled FO hollow fibers could be fully restored by simple physical cleaning. It was also found that hydrodynamic regime played an important role in combined organic–inorganic fouling of FO membranes.